Cytokines: Key Determinants of Resistance or Disease Progression in Visceral Leishmaniasis: Opportunities for Novel Diagnostics and Immunotherapy - Dayakar, Alti; Chandrasekaran, Sambamurthy; Kuchipudi, Suresh V.; Kalangi, Suresh K. (Frontiers in Immunology, 2019)
Leishmaniasis is a parasitic disease of humans, highly prevalent in parts of the tropics, subtropics, and southern Europe. The disease mainly occurs in three different clinical forms namely cutaneous, mucocutaneous and visceral leishmaniasis (VL). The VL affects several internal organs and is the deadliest form of the disease. Epidemiology and clinical manifestations of VL are variable based on the vector, parasite (e.g. species, strains, and antigen diversity), host (e.g. genetic background, nutrition, diversity in antigen presentation and immunity) and the environment (e.g. temperature, humidity, and hygiene). Chemotherapy of VL is limited to a few drugs which is expensive and associated with profound toxicity, and could become ineffective due to the parasites developing resistance. Till date, there are no licensed vaccines for humans against leishmaniasis. Recently, immunotherapy has become an attractive strategy as it is cost-effective, causes limited side-effects and do not suffer from the downside of pathogens developing resistance. Among various immunotherapeutic approaches, cytokines (produced by helper T-lymphocytes) based immunotherapy has received great attention especially for drug refractive cases of human VL. Therefore, a comprehensive knowledge on the molecular interactions of immune cells or components and on cytokines interplay in the host defense or pathogenesis is important to determine appropriate immunotherapies for leishmaniasis. Here, we summarized the current understanding of a wide-spectrum of cytokines and their interaction with immune cells that determine the clinical outcome of leishmaniasis. We have also highlighted opportunities for the development of novel diagnostics and intervention therapies for VL.